Proportional integral sliding mode control of hydraulic robot manipulators with chattering elimination - Azlan, N. Z.; Osman, Johari Halim Shah; Ahmad, Mohamad Noh (2006)
This paper is concerned with the application of a robust control approach based on Sliding Mode Control (SMC) strategy with proportional integral switching surface in controlling the position trajectory of a hydraulic manipulator. This paper also addresses the suppression technique for the undesirable chattering phenomenon which usually occurs in SMC by replacing the discontinuous controller sign function with a proper continuous function. Chattering is unwanted because it leads to an excessive usage and damages the actuators and therefore the control law may become impractical. In this study, an integrated model of hydraulically actuated robot that considers both the manipulator linkage and actuator dynamics is used to provide a more suitable model for controller synthesis and analysis. The control technique is stable in the large based on Lyapunov theory. Its performance is evaluated and compared with the existing Independent Joint Linear Control (IJC) technique through computer simulation. The results prove that the controller has successfully force the robot manipulator to track the desired position trajectory for all times and has better performance than IJC.